Dexamethasone-loaded scaffolds prepared by supercritical assisted phase inversion - Duarte, Ana Rita C. (2009)
The aim of this study was to evaluate the possibility of preparing dexamethasone-loaded starch-based porous matrices in a one-step process. Supercritical phase inversion technique was used to prepare composite scaffolds of dexamethasone and a polymeric blend of starch and poly(L-lactic acid) (SPLA) for tissue engineering purposes. Dexamethasone is used in osteogenic media to direct the differentiation of stem cells towards the osteogenic lineage. Samples with different drug concentrations (5–15 wt.% polymer) were prepared at 200 bar and 55 C. The presence of dexamethasone did not affect the porosity or interconnectivity of the polymeric matrices. Water uptake and degradation studies were also performed on SPLA scaffolds. We conclude that SPLA matrices prepared by supercritical phase inversion have a swelling degree of nearly 90% and the material presents a weight loss of 25% after 21 days in solution. Furthermore, in vitro drug release studies were carried out and the results show that a sustained release of dexamethasone was achieved over 21 days. The fitting of the power law to the experimental data demonstrated that drug release is governed by an anomalous transport, i.e., both the drug diffusion and the swelling of the matrix influence the release of dexamethasone out of the scaffold. The kinetic constant was also determined. This study reports the feasibility of using supercritical fluid technology to process in one step a porous matrix loaded with a pharmaceutical agent for tissue engineering purposes.